The excess profits during Covid-19 and their tax revenue potential - Evgeniya Dubinina; Javier Garcia-Bernardo; Petr Janský (Charles University in Prague, Institute of Economic Studies (IES), 2022)
The COVID-19 pandemic has affected most companies' profits negatively, but other companies did exceptionally well, recording excess profits during the pandemic. In this paper we estimate the scale of these excess profits, their determinants, and the revenue potential of excess profits tax. To estimate excess profits, we develop a trend-adjusted average earnings methodology. We apply the methodology to the consolidated Orbis data to estimate that large multinational corporations (MNCs) with subsidiaries in the EU made excess profits of 447 billion in 2020 (41.7% of their total profits in 2020). We show that primary business activities is a key determinant of MNCs' excess profits made during the COVID-19 pandemic. We show that manufacturing, information, and financial sectors are responsible for the majority of excess profits. With country-by-country reporting data we estimate the excess profits arising from each EU member state and find that EU member states could together raise 6 billion with an excess profits tax of 10%, an additional tax levied by governments on corporations' excess profits. The research findings may be useful for policymakers in addressing the question of financing economic recovery from the COVID-19 pandemic.
Keywords: H25; L11; L25; 330; excess profits; covid-19; multinational corporations; excess profits tax; european union